Hymn do Hermesa. Elementy komiczne czy mim? - Korus, Kazimierz (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The author presents the results of his analysis of the hymn, concluding that it is based on the composition of a mime. The following supports his belief: 1. The scene is composed through drama. The dialogue and action dictate its structure. The omniscient narrator plays an important role here through his introduction to the scene, his statements and descriptions, and, most importantly, with his comments which suggest the perception of the scene by participants, who like Apollo and Zeus react with laughter to the infant (Hermes’) behaviour. We can then name the whole composition a diegetic mime. 2. The intention of the scene is that of all mime authors, to provoke listeners to laughter, and to create the atmosphere of a play (gelotopoiéin). 3. The comics of the scene have the exact moral function – to create understanding between the arguing gods (Hermes and Apollo). This function is characteristic of the author of Iliad and especially Odyssey (agreement between Euryalos and Odysseus). 4. The main theme, adopted later by mime and comedy, is a quarrel (presented here with a teasing perspective – what is underlined in the description of reaction and the contrasting stylization of Hermes’ and Apollo’s speeches). An unexpected form (para prosdokían) comes in the over-colouristic characteristics of the players (an infant bearing adult characteristics, beginning with smart talk, mischievous persuasive arguments and ending with thieving behaviour); there is also the topos of releasing winds, and insults and proverbial statements are very important for epic compositionin provoking laughter.
Keywords: hymny homeryckie; Hymn do Hermesa; komedia; mim